Analisis Gas Hasil Pembakaran Tungku Gasifikasi Tongkol Jagung - Adoe, Dominggus G. H.; Jasron, Jahirwan Ut; Nahak, Jufrianus Aven; Riwu, Defmit B.N. (Universitas Nusa Cendana, 2022)
As an agricultural country, Indonesia has an abundant biomass energy source. One of the potential agricultural wastes to be processed into alternative fuels is corn cobs. Therefore, the purpose of his study was to compare the mass of corn cobs, namely 4 kg, 8 kg, and 12 kg, to gas produced by gasification at a temperature of 100-180 ºC. The results of the study showed that the gas produced by gasification of corn cobs with a mass of 4 kg, 8 kg, and 12 kg had a percentage of gas that tends to decrease with increasing fuel mass, namely 8 kg and 12 kg, the decrease caused by several factors, including the relative moisture content, high and low combustion temperatures. And the efficiency resulting from the combustion of the gasification furnace with mass variations, namely: 4 kg = 96,8843 %, 8 kg = 88,1387 % dan 12 kg = 88,1485%.